Development and characterisation of sodium alginate and HPMC films for mucosal drug delivery. (8th November 2010) - Rai, Dinesh; Maniruzzaman, Mohammed; Boateng, Joshua S.
The aim of this work was to develop and evaluate sodium alginate (SA) and hydroxypropyl methylcellulose (HPMC) films as novel drug delivery systems for moist surfaces such as wounds, buccal and vaginal cavities. Films containing SA or HPMC and PEG 200 or glycerol were prepared by a solvent casting technique. Process optimisation was performed to establish the best experimental parameters for preparing the films. Physical appearance, ease of removal, tensile properties (tensile strength, % strain at break) and plasticiser leaching were investigated. These criteria formed the basis for further development formulations comprising optimum ratios of SA/HPMC and PEG 200/glycerol. The optimum polymer-plasticiser combinations were then selected for further characterisation of tensile, hydration, adhesive properties by texture analysis and surface morphology by scanning electron microscopy. The results showed the potential of developing both fast and controlled release mucosal formulations by a combination of the two polymers.